The Counseling Role of Social Workers in the Electronic Reality of Cyber Security - Aladra, Ibrahim Ahmed (Dirasat: Human and Social Sciences, 2025)
Objective: This study aimed to explore the key advisory roles of social workers in the context of modern cybersecurity, focusing on developmental, preventive, and intervention roles, as well as the challenges they face. Methods: A qualitative research approach was employed, with a sample of 30 specialists and practitioners working in cyber-security, network security, and information security. Data were collected through interviews as the primary tool. Results: The findings highlighted the most prominent developmental (constructive) roles, including raising awareness, providing training to diverse societal groups, and acting as mediators for the exchange of scientific information. Key preventive roles identified were the enactment and enforcement of regulatory legislation and networking with related community institutions. As for intervention (therapeutic) roles, they included designing supportive professional programs and consulting external experts. The main challenges facing social workers were a lack of sufficient understanding of their importance and roles in the cybersecurity and information security domains, as well as the novelty of the field, leading to a shortage of mechanisms and action plans. Conclusions: The study recommended establishing an administrative and social unit within organizations working in cybersecurity and network security to enable social workers to practice their profession with a high degree of professionalism and specialization.